Book review: The Enlightened Social Worker: An Introduction to Rights-Focused Practice. By Donald Forrester, Publisher: Bristol University Press, ISBN: 978-1-4473-6767-3 - Aleksandra Jadwiszczok (Scottish Journal of Residential Child Care)
In The Enlightened Social Worker, Forrester skilfully pulls together the themes of conflict vs rights, a dilemma which so often occurs within social work practice and explains not only the complex nature of social work but also the significance of the humanistic part of our work, which directly interlinks with person-centred care as the quintessence of social work practice. The book also explores the complexity of social work practice and a relationship between working to uphold service users’ rights and the instances where these rights can become conflicted, demonstrating that it lies within a social worker’s role to resolve these conflicts. Therefore, there is a need for social workers to understand human rights and the significance of these being upheld. At the same time, social workers must consider and value service users’ views in their practice and must often look beyond the helping part of the profession, as they carry out assessments and weigh up the options available in order to reach the most feasible decisions.